2022
DOI: 10.15388/amed.2021.29.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Against COVID-19 Disease During Pregnancy

Abstract: Background. The effect of COVID-19 disease during pregnancy is still under investigation, however scientific studies have shown that pregnant women with COVID-19 infection are at increased risk for severe illness or complications [1]. Risk factors for severe disease and death in pregnancy include maternal age (especially ≥35 years), obesity, preexisting medical comorbidities (particularly hypertension and diabetes or more than one comorbidity), and being unvaccinated [2]. Many societies of obstetricians and gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…We included 16 studies (425 867 women) reporting SARS-CoV-2 infection-related outcomes6 7 17 19 21 31 33 36 38–45 and 35 (1 362 172 women) reporting pregnancy-related maternal and offspring outcomes in the secondary analysis 17 18 21–24 29–34 36 38 39 41–60. Twenty-three studies reported reactogenicity outcomes (94 206 women) following vaccination 38 39 46 61–80…”
Section: Resultsmentioning
confidence: 99%
“…We included 16 studies (425 867 women) reporting SARS-CoV-2 infection-related outcomes6 7 17 19 21 31 33 36 38–45 and 35 (1 362 172 women) reporting pregnancy-related maternal and offspring outcomes in the secondary analysis 17 18 21–24 29–34 36 38 39 41–60. Twenty-three studies reported reactogenicity outcomes (94 206 women) following vaccination 38 39 46 61–80…”
Section: Resultsmentioning
confidence: 99%